Improving water absorption time and the natural silk strength (Bombyx Mori) using atmospheric dielectric barrier discharge plasma - Zaenul Muhlisin; Muhammad Adrian Lathif; Fajar Arianto; Pandji Triadyaksa (Journal of Physics and Its Applications, 2021)
This researchaimed to obtain Dielectric Barrier Discharge plasma discharge characteristics with and without the placement of natural silkBombyx Mori on one of the electrodes. Furthermore, the strength and the water absorption time of the irradiated silk samples will be analyzed.  Plasma discharge is generated by connecting electrodes of point-to-plane configuration with a sheet of glass inserted on the plane electrode at atmospheric conditions. The characterization of plasma discharge, either with or without the natural silk samples' placement on the plane electrode, was performed by increasing A.C.'s high voltage power source to reach arch discharge. Theelectrode spacing varied from 0.7 cm to 2.5 cm with a 0.3 cm increment. Sample irradiation was performed using cold plasma for 5, 15, and 30 minutes respectively. Placing or not placing the natural silk samples on the plane electrode will increase the plasma's discharge current and increase the high voltage. Moreover, increasing the distance between the electrodes and placing the sample on the plane electrode decreases the discharge current. Using Scanning Electron Microscopy, it was found that increasing plasma irradiation time on samples decreases the silk thread'sdiameterand shortening its water absorption time. The strength of irradiated fabric was reduceduntil 15 minutes of irradiation. However, at 30 minutes of irradiation, there was an increase in sample thickness compared to control samples.